Investigation of the effect of coronary collateral circulation quality on postoperative atrial fibrillation after coronary artery bypass graft operations in patients with right coronary artery total occlusion - Abanoz, Mustafa; Yavuz, Senol (The European Research Journal, 2022)
Objectives: Postoperative atrial fibrillation (PoAF) may occur in 25-50% of patients after coronary artery bypass graft (CABG) surgery. The severity of coronary artery disease and the quality of coronary collateral circulation (CCC) in the coronary artery with chronic total occlusion (CTO) are known as indirect indicators of myocardial ischemia. In this study, we aimed to investigate the effect of CCC quality on PoAF in patients with right coronary artery (RCA) total occlusion who underwent CABG operation. Methods: Patients who underwent isolated CABG operation between May 15, 2016 and June 15, 2020 and had RCA CTO were included in the study retrospectively. The patients were recorded as Group 1 who developed PoAF in the postoperative period and Group 2 who did not. Results: A total of 99 patients were included in the study. Those who develop PoAF were determined as Group 1 (n = 32, mean age = 66.9 ± 11 years), and those who did not were determined as Group 2 (n = 67, mean age = 54.4 ± 12.8, years). There were no statistically significant differences between the two groups in terms of gender, smoking, diabetes mellitus, hypelipidemia and chronic obstuctive pulmonary disease rates. In multivariate analysis, being over 70 years old (OR: 1.396, 95% CI: 1.080-2.190, p = 0.007), poor CCC (OR: 1.090, 95% CI: 1.045-1.338, p = 0.014) and left atrial diamater (OR: 0.557, 95% CI: 0.471-0.783, p = 0.032) were determined as independent predictors of development of PoAF. Conclusions: In this current study, we demonstrated that low CCC quality increases the risk of POAF in patients with right coronary CTO. CCC quality can be used as an evaluation parameter in identifying groups at risk for PoAF in these special patient groups.